Editorial overview: Endocrine and metabolic adaptations to extreme environments: Living life to the extreme – insights into the limits of life and transitions to disease - Larcombe, Alexander; Wyrwoll, C. (2020)
Understanding the underlying endocrine and metabolic changes to extreme conditions reveal important biological responses, biological limits under healthy conditions, and critical signals of transition toward disease. Recent research is also starting to reveal how humans and animals have some capacity to ‘adapt’ to extreme conditions, particularly in instances where the exposure is time-limited. However, as we enter a period of even greater climate change and uncertainty and as we continue to ‘reach for the stars,’ in both the literal sense via space exploration and metaphorically in terms of our exploration and exploitation of more extreme environments on Earth, the option to escape or avoid extreme environments becomes less possible. The need to understand responses to extreme environments has prompted this edition of Current Opinion in Endocrine and Metabolic Research.